Gender features of alcohol use with harmful consequences in mental and physical pathology in family medicine practice - Salden’ Вікторія (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the Scientific-practical сonference "Psychosomatic medicine: science and practice". It is dedicated to gender features of alcohol use with harmful consequences in mental and physical pathology in family practice.